Palladium-catalyzed cross-coupling reaction of alkenyl bromides with potassium alkyltrifluoroborates - Molander, Gary A.; Ham, Jungyeob; Seapy, Dave G. (PERGAMON-ELSEVIER SCIENCE LTD, 2007)
The Suzuki-Miyaura-type cross-coupling reaction of potassium alkyltrifluoroborates with various alkenyl bromides in the presence of 10 mol % of PdCl2(dppf)center dot CH2Cl2 and 3.0 equiv of Cs2CO3 in aqueous toluene at 80 degrees C provided the desired compounds in 63-95% yields. A variety of functional groups in the potassium alkyltrifluoroborates were tolerated under the basic conditions. (c) 2006 Elsevier Ltd. All rights reserved.
Keywords: EXPANDING ORGANOBORON CHEMISTRY; EFFICIENT AGENTS; ARYL; DERIVATIVES; CROTYLATION; ALLYLATION; ALDEHYDES; CHLORIDES